Large Eddy Simulation of advancing rotor for near to far wake assessment - Caprace, D.-G.; Buffin, S.; Duponcheel, M.; Chatelain, P.; Winckelmans, G. (My University, 2017)
The present work focuses on the Large Eddy Simulation of the wake ow behind an advancing rotor, to support the investigation of rotorcraft wake characteristics and decay mechanisms. A mixed Lagrangian-Eulerian Vortex Particle-Mesh (VPM) method was employed to simulate the near to far wake development of a four-bladed rotor. The rotor configuration was chosen to mimic the set-up of the high advance ratio experiment on an articulated rotor conducted at the University of Maryland in 2014. For an advance ratio of 0.41, results on trim control inputs are compared between the present simulations and the experiment. Then, the wake generation and development mechanisms are described (i) qualitatively in terms of vortex dynamics using rotor polar plots and 3D visualizations; (ii) quantitatively using classical integral diagnostics. A preliminary analysis shows that the strength of the emerging wake vortices increases over the first 30 diameter distance behind the rotor. This behavior is traced back to a longitudinal alignment of vorticity, driven by vortex stretching.